The Effect of Dhikr on Preoperative Anxiety Among Women Undergoing Elective Cesarean Section: A Pre-Experimental Study - Bagus Ulin Nuha; Akhmad Safi'i; Mukhamad Rajin; Ninik Azizah (Jurnal Kesehatan Komunitas Indonesia, 2025)
Preoperative anxiety in women undergoing cesarean section (CS) is a common problem that can affect physical and psychological conditions, including increased blood pressure, heart rate, and stress hormones, which can interfere with the surgical process and postoperative recovery. Spiritual approaches such as dhikr (Islamic prayer chanting) have been shown to calm the mind, improve emotional stability, and enhance patients' mental readiness before surgery. This study employed a single-group pretest-posttest pre-experimental design with 15 respondents from the Central Surgical Unit of Islamic Hospital of Nahdlatul Ulama (NU) Demak selected through purposive sampling. The dhikr intervention was conducted for 10 minutes, guided by a nurse before surgery. Anxiety levels were measured before and after the intervention using the Amsterdam Preoperative Anxiety and Information Scale (APAIS). The average anxiety score decreased from 24.6 before the intervention to 14.07 after the dhikr, and the Wilcoxon Signed-Rank test (Z = -3.413, p = 0.001) showed a statistically significant decrease. These results indicate that spiritual interventions, including dhikr (remembrance of God), are effective in reducing preoperative anxiety by increasing psychological and physiological calm. These findings support the integration of dhikr into holistic nursing care to enhance psychological stability and mental readiness in patients.